A Study on Morphometric and Mouth Structure of Luciocephalus pulcher Gray, 1830 from the Sibam River, Pekanbaru - Putri, Dwika Hanifah; Efawani, Efawani; Windarti, Windarti (Jurnal Perikanan dan Kelautan, 2025)
Luciocephalus pulcher lives in peat swamps, and the male incubates the eggs in the mouth. A study aimed to determine morphometric characters and differences in the oral structure of male and female fish was conducted from June to July 2024. Fish samples were caught in the upper Sibam River. 5 times, once/week. The morphometrical characteristics were measured, and the fish mouth structure was observed. Results showed that 32 fish were caught, consisting of 21 males and 11 females. Of the 37 morphometric characters observed, 18 differed between males and females. These characters included total length, head length, body height, caudal peduncle height, eye diameter, anal fin to caudal fin base distance, dorsal fin base length, pectoral fin base length, anal fin height, ventral fin base length, caudal fin base length, lower jaw length, upper jaw length, lower jaw width, gular sac width, lower lip length and upper lip length. The total length of male fish ranged from 48-135 mm, while females were 48-135 mm. Fin characteristics in male and female fish were the same, with the formula D.I, 8-12 P.12-15 V.6-7 A.I, 14-20 C.13-15. The difference in mouth characters was seen in the gular sac. The gular sac of male fish was wider with thicker tissue, more folded, more flexible, elastic skin tissue, and smaller, more flexible hyoid bone. In contrast, female fish have smaller, less elastic gular sacs, thinner tissue, and less folded and thicker hyoid bone.